English Composition As A Happening - Sirc, Geoffrey (University Press of Colorado, 2002)
What happened to the bold, kicky promise of writing instruction in the 1960s? The current conservative trend in composition is analyzed allegorically by Geoffrey Sirc in this book-length homage to Charles Deemer's 1967 article, in which the theories and practices of Happenings artists (multi-disciplinary performance pioneers) were used to invigorate college writing. Sirc takes up Deemer's inquiry, moving through the material and theoretical concerns of such pre- and post-Happenings influences as Duchamp and Pollock, situationists and punks, as well as many of the Happenings artists proper. With this book, already a cult classic, began a neo-avant-garde for composition studies. Winner of the Ross W. Winterowd Award for most outstanding book in composition theory.